2016
DOI: 10.1186/s12879-016-1593-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil-transmitted helminth infections and leprosy: a cross-sectional study of the association between two major neglected tropical diseases in Indonesia

Abstract: BackgroundThe clinical spectrum of leprosy is dependent on the host immune response against Mycobacterium leprae or the newly discovered Mycobacterium lepromatosis antigen. Helminth infections have been shown to affect the development of several diseases through immune regulation and thus may play a role in the clinical manifestations of leprosy and leprosy reactions. The purpose of this study is to determine the proportion of helminth infections in leprosy and its association with the type of leprosy and type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…5,23 As both vitamin A deficiency and helminth infections are associated with suppression of the Th1 immune response, theoretically, a higher risk of T2R and possibly lower risk of T1R could be hypothesized. This fits with the results of Oktaria et al, 13 who found an increased risk of T2R in helminth-positive patients in Indonesia. Another study (Hagge et al) investigated helminth coinfection and reactions in Nepal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5,23 As both vitamin A deficiency and helminth infections are associated with suppression of the Th1 immune response, theoretically, a higher risk of T2R and possibly lower risk of T1R could be hypothesized. This fits with the results of Oktaria et al, 13 who found an increased risk of T2R in helminth-positive patients in Indonesia. Another study (Hagge et al) investigated helminth coinfection and reactions in Nepal.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10][11][12] A recent cross-sectional study in Indonesia showed an association between soil-transmitted helminths (STH) and a higher occurrence of T2R. 13 This study also showed a higher odds of STH in multibacillary (MB) versus paucibacillary leprosy cases, an association which Diniz et al 14 also demonstrated in Brazil. On the other hand, Hagge et al 15 found a lower risk of reactions in STH-positive participants.…”
Section: Introductionmentioning
confidence: 71%
“…Infection with M. leprae or M. lepromatis causes leprosy, a chronic granulomatous infectious disease. A study of Indonesian patients infected with M. lepromatis reported that those with gastrointestinal helminth infections (e.g., T. trichiura, Stongyloides sterocalis ) similarly presented with more severe types of leprosy ( 65 ).…”
Section: Effects On Bacterial Infectionsmentioning
confidence: 99%
“…Additionally, those who receive therapeutic deworming without concomitant infrastructure changes such as sanitation improvements are at high risk for re-infection within co-endemic settings. A recent small study reported microscopy STH + association with ENL ( Oktaria et al, 2016 ). Confoundingly for comparisons, however, the 8 with either active or historical ENL were grouped (two very different immunological states), all of which had received extended corticosteroid treatment prior to sampling.…”
Section: Discussionmentioning
confidence: 98%